Clinical course of isolated distal deep vein thrombosis in patients with active cancer: a multicenter cohort study. (18th July 2017) - Dentali, F.; Pegoraro, S.; Barco, S.; di Minno, M. N. D.; Mastroiacovo, D.; Pomero, F.; Lodigiani, C.; Bagna, F.; Sartori, M.; Barillari, G.; Mumoli, N.; Napolitano, M.; et al.
Abstract : Essentials Isolated distal deep vein thrombosis (IDDVT) is frequently associated with cancer. No study has specifically evaluated the long‐term clinical course of cancer‐associated IDDVT. Patients with cancer‐associated IDDVT are at very high risk of symptomatic recurrence and death. We observed low rates of major bleeding during anticoagulation. Summary: Background: Although isolated distal deep vein thrombosis (IDDVT) is frequently associated with cancer, no study has specifically evaluated the long‐term clinical course of IDDVT in this setting. Aim: To provide data on the rate of recurrent venous thromboembolism (VTE), major bleeding events and death in IDDVT patients with active cancer. Patients and Methods: Consecutive patients with active cancer and an objective IDDVT diagnosis (January 2011 to September 2014) were included from our files. We collected information on baseline characteristics, IDDVT location and extension, VTE risk factors, and type and duration of anticoagulant treatment. Results: A total of 308 patients (mean age 66.2 [standard deviation (SD), 13.2 years]; 57.1% female) with symptomatic IDDVT and a solid ( n = 261) or hematologic ( n = 47) cancer were included at 13 centers. Cancer was metastatic in 148 (48.1%) patients. All but three (99.0%) patients received anticoagulant therapy, which consisted of low‐molecular‐weight heparin in 288 (93.5%) patients. Vitamin K antagonists were used for the long‐term treatment in 46 (14.9%) patients, whereas all others continued the initial parenteral agent for a mean treatment duration of 4.2 months (SD, 4.6 months). During a total follow‐up of 355.8 patient‐years (mean, 13.9 months), there were 47 recurrent objectively diagnosed VTEs for an incidence rate of 13.2 events per 100 patient‐years. During anticoagulant treatment, the annual incidence of major bleeding was 2.0 per 100 patient‐years. Conclusions: Cancer patients with IDDVT have a high risk of VTE recurrence. Additional studies are warranted to investigate the optimal intensity and duration of anticoagulant treatment for these patients.